Equal treatment education-training and social equality practice upon maritime students and professionals - A literature review identifying facilitators and barriers - Blomqvist, Anna-Karin; Folkesten, David (My University, 2021)
Background With diversity in equal treatment education-training and social equality practice upon maritime students and professionals, this study aimed to conduct a global situation analysis, through an integrated literature review, to identify the facilitators and barriers in equality to improve social equality practice for maritime students and professionals. Methods By using an integrative review we conducted a systematic literature review including the five key stages of; problem identification, literature search, data evaluation, data analysis, and presentation of results. The literature searches were conducted in databases and a deductive data analysis against equality was performed. Results The search identified 223 articles, of which 23 articles were included. For social equality practices, the main barrier between education, regulation, and the labour market was identified. Education has come far to improve equality whilst the market does it voluntarily based on economic circumstances and stereotypes. Structural mechanisms such as regulations, leadership, and future technologies can facilitate an equal level of social equality for all. Conclusions The barrier between theory and practice for maritime students and professionals is due to a will to sustain systems. There is hope for the future through education and training and with the individual will to change attitudes, also worldwide policies can pave the way for a change that will take time. Training ashore, at ships, and face to face is suggested for leaders, managers, maritime students, and professionals based on barriers identified in this study.
Keywords: maritime; seafarer; equality; training; education; status; rights; opportunities